Childhood leukemia a practical handbook - Reaman, Gregory H.; Smith, Franklin O. (Pediatric oncology., 2011)
This book is a comprehensive and up-to-date compendium on all aspects of childhood acute lymphoblastic and acute myeloid leukemia, which together constitute the most frequent cancer in the pediatric age group. After introductory chapters on the epidemiology and biology of pediatric leukemia, treatment considerations are extensively reviewed, with emphasis on the use of risk-adjusted treatment approaches. Promising targeted agents are discussed, and strategies for the development of new agents are appraised. The late effects of leukemia and its therapy are then considered in depth, with due attention to management of the psychosocial impact of the disease. Finally, global strategies to improve leukemia care and outcome are reviewed, and future directions discussed. The authors are internationally recognized experts and offer a largely evidence-based consensus on etiology, biology, and treatment. This handbook has far-reaching applicability to the clinical diagnosis and management of pediatric leukemia and will prove invaluable to specialists, generalists, and trainees alike.